Pharmacokinetic profile of promising acetylcholinesterase reactivators K027 and K203 in experimental pigs - Karasova, Jana Zdarova; Kvetina, Jaroslav; Tacheci, Ilja; Radochova, Vera; Musilek, Kamil; Kuca, Kamil; Bures, Jan (Toxicology letters, 2017)
Standard treatment of organophosphorus compounds (OPs) poisoning includes administration of an anti-muscarinic (atropine), anticonvulsive (diazepam) and acetylcholinesterase reactivator (oxime). From a wide group of newly synthesized oximes, oxime K027 and oxime K203 seem to be perspective compounds in some specific OPs intoxication. The available in vitro and in vivo preclinical data indicate that both oximes may be considered for potential human use. The main aim of this study was to establish plasmatic concentration curves of both oximes after intramuscular (i.m.) and intragastric (i.g.) application with subsequent pharmacokinetic analysis and study distribution after (i.m.) application on a non-rodent animal model (experimental pigs; 1500mg/animal). According to the results, both oximes had similar Cmax (K027: 106±19μg/mL and K203: 111±8μg/mL) in Tmax 19±5min, respectively, in 22±3min. Bioavailability of oxime K027 calculated as AUCtotal (8389±1024minμg/mL) was halved compared to oxime K203 (16938±795minμg/mL). The highest concentration from peripheral tissues was found in the kidney and lung, but the brain concentrations stay very low, the plasma/brain ratio being approximately 1%. The applied doses were derived from the recommendation where it is possible to use three autoinjectors to save human life. The results provide us with knowledge about the pharmacokinetics and distribution of these new oximes and may help us to better estimate the human pharmacokinetic profile.
Keywords: Animals; orgánová specificita; Acetylcholinesterase; Female; Tissue Distribution; ženské pohlaví; oximy; Sus scrofa; Pyridinium Compounds; vysokoúčinná kapalinová chromatografie; pyridinové sloučeniny; Injections, Intramuscular; injekce intramuskulární; Chromatography, High Pressure Liquid; Oximes; acetylcholinesterasa; aplikace orální; reaktivátory cholinesterasy; tkáňová distribuce; Organ Specificity; plocha pod křivkou; Administration, Oral; zvířata; Cholinesterase Reactivators; Area Under Curve